Chemical evaluation of bovine colostrum preserved by different methods in a hot climate - MBUTHIA, E W; GACHUIRI, C K; ABATE, A (The Indian Journal of Animal Sciences, 2014)
Colostrum of cows of the Sahiwal breed was preserved for 1 month at 28Â°C by 5 different methods viz, treatment with formaldehyde at levels of 0.1 % and 0.05%; addification with formic acid at levels of 0.5% and 0.1 %; and an untreated control. Weekly aliquots were analyzed for total solids, crude protein, lactose, pH and titratable acidity. Nonprotein nitrogen determination was carried out every 2 weeks. There was no Significant change in crude protein and total solids content of the colostrums in all the treatment methods. Non-protein nitrogen increased significantly in all treatment groups with the highest increases being recorded in the naturally fermented and the formic acid-treated colostrum batches. The pH decreased and titratable acidity increased most rapidly in the untreated colostrum and least of all in the formalde-hydetreated colostrum. Decrease of lactose was most pronounced in the untreated colostrum.